Robinija (Robinia pseudoacacia L.) in njen les - Torelli, Niko (Les (Ljubljana), 2002)
Details are given of the anatomical structure and its relation to wood properties and use. The possibility of the existance of the conducting and storage sapwood is discussed.
Keywords: robinija; struktura lesa; les; lastnosti